What should be the goal blood pressure in nondiabetic chronic kidney disease? - Schneider, Markus P.; Hilgers, Karl Friedrich (Current Opinion in Nephrology and Hypertension, 2014)
To summarize the available evidence on whether a lower blood pressure (BP) treatment target can ameliorate the progression of nondiabetic chronic kidney disease (CKD), and prevent cardiovascular events in CKD patients.The three prospective, randomized controlled trials which addressed the question of progression of CKD suggest that a lower BP treatment goal (<130/80 mmHg) may lead to better preservation of renal function, but only in those patients with proteinuria of more than 300 mg/day. However, the evidence is not conclusive. We are not aware of adequately powered, randomized trials that have assessed the efficacy of lower target BP levels for the prevention of cardiovascular events specifically in nondiabetic CKD patients. The available circumstantial evidence (e.g., subgroup analyses of CKD patients in cardiovascular trials) fails to reveal a clear benefit of a lower BP goal.There is currently no convincing evidence to recommend a lower than standard BP treatment target of less than 140/90 mmHg for all patients with nondiabetic CKD. A lower treatment target of less than 130/80 mmHg may delay renal disease progression but only in patients with proteinuria.
EVALuna2:3702